2021
DOI: 10.1002/ar.24779
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture in promoting neural repair after spinal cord injury: Inhibiting the Notch signaling pathway and regulating downstream proteins expression

Abstract: Spinal cord injury (SCI) is one of the serious central nervous system injuries and the incidence of SCI continues to increase. Previous studies have indicated that electroacupuncture (EA) is beneficial for promoting recovery after SCI. In the present study, we attempted to evaluate how EA can promote the neural repair in SCI model rats by observing changes in the Notch signaling pathway. Experimental rats were randomly divided into four groups. Each group had its own intervention period: 1 day, 7 days, 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The upregulation of exosomal miR-146b, NeuroD1, the activation of the Notch pathway, and the downregulation of the PTEN expression are associated with acupuncture-induced improvement of neurological injury after ischemic stroke ( Tao et al, 2014 ; Zhao et al, 2015 ; Sha et al, 2019 ; Zhang et al, 2020 ). In contrast, the potential signals of the acupuncture-induced NSC regulation in the SCI model include Wnt/β-catenin ( Zhang et al, 2017a ), ERK ( Xu et al, 2019 ), miR-449a ( Zhu et al, 2017 ), and Notch pathway ( Wang et al, 2021b ). Third, electroacupuncture reinforces the survival and synaptogenesis of transplanted NSC-derived neural network scaffolds as a neuronal relay bridging two severed ends of the injured spinal cord ( Jin et al, 2019 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…The upregulation of exosomal miR-146b, NeuroD1, the activation of the Notch pathway, and the downregulation of the PTEN expression are associated with acupuncture-induced improvement of neurological injury after ischemic stroke ( Tao et al, 2014 ; Zhao et al, 2015 ; Sha et al, 2019 ; Zhang et al, 2020 ). In contrast, the potential signals of the acupuncture-induced NSC regulation in the SCI model include Wnt/β-catenin ( Zhang et al, 2017a ), ERK ( Xu et al, 2019 ), miR-449a ( Zhu et al, 2017 ), and Notch pathway ( Wang et al, 2021b ). Third, electroacupuncture reinforces the survival and synaptogenesis of transplanted NSC-derived neural network scaffolds as a neuronal relay bridging two severed ends of the injured spinal cord ( Jin et al, 2019 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…EA stimulation was reported to regulate the function of SCs, which favors axonal recovery post-SCI [ 16 ]. Through regulating Notch signaling pathway, EA was found to promote the recovery following SCI in rats [ 9 ]. The effectiveness of EA in treating trauma has also been demonstrated [ 17 ], but its possible mechanism in SCI still needs to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, a traditional Chinese medicine, has found a broad application in the treatment of various neurological diseases. As an improved variant of acupuncture approach, electroacupuncture (EA) had been reported to be efficacious in treating various SCI-related symptoms [8] [9][10][11][12][13]. Combined treatment of EA and curcumin improves the recovery of motor function and regulates oxidative stress in rats after traumatic SCI [14].…”
Section: Introductionmentioning
confidence: 99%
“…This showed that acupuncture is already widely accepted in the international pain field. Acupuncture has also been successfully used for the treatment of central neuropathic pain, as studies have shown that acupuncture can improve the neurologic or functional recovery after spinal cord injury (Tan et al, 2021; Wang et al, 2021; Wong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%